ПЕРВЫЕ РЕЗУЛЬТАТЫ ДЕКАМЕТРОВОГО ОБЗОРА СЕВЕРНОГО НЕБА. РЕДЕТЕКТИРОВАНИЕ ИЗВЕСТНЫХ ПУЛЬСАРОВ - Захаренко, В. В; Васильева, Я. Ю.; Коноваленко, А. А.; Зарка, Ф.; Николаенко, В. С. (Одеські астрономічні публікації, 2011)
At the UTR-2 radio telescope the survey of northern sky is being conducted with aim to search for pulsars and transients. In the first stage the detection of a complete list of known pulsars with parameters DM -3, period more than 0.1 s and declination above -10° was carried out. For the first time in the decameter range more than a half of known pulsars with the aforementioned parameters (40 of 74) have been detected, whereas before there were known only about 10 of them. An average exponent value for the frequency dependence of scattering time constant for the detected pulsars was obtained. It is equal 4.18. Also, the value of the radiation cone broadening was estimated. With decreasing of frequency from 100 to 25 MHz for pulsars with period of < 1 s the extension is equal 2.2, and with period of > 1 s – 1.6 times. Obtained results give a hope for finding a significant number of pulsars and transient sources of radiation in the ongoing survey.